Seasonal Variation in Interest Rates - Barth, James R.; Bennett, James T. (The Review of Economics and Statistics, 1975)
A survey of the empirical work involving interest rates indicates an almost universal use of seasonally unadjusted rates, apparently due to a conviction that seasonal factors are not important in interest rates. Studies by V. Kerry Smith and Richard Marcis (1972), Stanley Diller (1969) and William Gibson (1970), however, provide evidence showing that interest rates exhibit seasonal variation. Seasonality in interest rates merits careful consideration for at least two reasons. First, as noted by Gibson, An aim of the Federal Reserve System is to accommodate seasonal swings in the financial needs of trade, and the system tries to do this by removing seasonal fluctuations from interest rates. The seasonal variations remaining in interest rates suggest that the system is not wholly successful in these efforts. . (Gibson, 1970, p. 442). Second, from an econometric point of view, any model, such as a money demand model, which contains an interest rate as an independent variable should also contain seasonal dummy variables; otherwise, the coefficient of the interest rate variable may be both biased and inconsistent.' These issues underscore the importance of determining whether there is seasonality in interest rates. In this regard, it is interesting to note that the Federal Reserve does not report seasonally adjusted rates, apparently because the Board does not recognize the existence of a seasonal component. The purpose of this paper is to provide additional information regarding seasonality in interest rates. Unlike earlier studies, both daily and monthly data are analyzed. And, whereas Smith and Marcis employed spectral analysis to detect seasonality, ordinary least squares techniques with seasonal dummies are employed here. Using this technique, we find, in contrast to the findings reported by other investigators, no evidence of a significant seasonal component in monthly rates. Seasonality is, however, present in the daily rate. The plan of the remainder of the paper is as follows. In section II, the magnitude and the importance of seasonality in three interest rates are assessed. Section III contains a discussion of seasonal variation in a short-term rate employing daily as opposed to monthly data. A summary and the conclusions are presented in the last section.